2015
DOI: 10.3171/2014.10.jns132369
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and long-term outcomes of moyamoya disease: a single-center experience with 528 cases in China

Abstract: OBJECT The aim of this study was to describe the baseline clinical features and long-term outcomes of patients with moyamoya disease (MMD) based on a 25-year period at a single center in China. METHODS  Data obtained in 528 consecutive patients with MMD treated at the authors' hospital from 1984 to 2010 were reviewed retrospectively. Events of transient ischemic attack, new infarction, and hemorrhage were included. The Kaplan-Meier risk of stroke was calculated. RESULTS  The mean (± SD) patient age was 26 ± … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
61
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(68 citation statements)
references
References 27 publications
5
61
0
2
Order By: Relevance
“…1 ticular, recurrent hemorrhage was observed in 5 patients. In several past large studies, the incidence of recurrent stroke after revascularization was reported to be approximately 5-20% (annual risk: 0.4-6.7%) [11][12][13][14][15][16]. It is difficult to directly compare these incidences because the included patients' characteristics, follow-up rate, or management made a difference to the incidence of recurrent stroke in our study.…”
Section: Relationship Between the Rnf213 Genotype And Long-term Clinimentioning
confidence: 70%
“…1 ticular, recurrent hemorrhage was observed in 5 patients. In several past large studies, the incidence of recurrent stroke after revascularization was reported to be approximately 5-20% (annual risk: 0.4-6.7%) [11][12][13][14][15][16]. It is difficult to directly compare these incidences because the included patients' characteristics, follow-up rate, or management made a difference to the incidence of recurrent stroke in our study.…”
Section: Relationship Between the Rnf213 Genotype And Long-term Clinimentioning
confidence: 70%
“…Then, 8 records were excluded for no data. Finally, 16 articles were included, 7,8,1124 among which 8 articles compared the efficacy of conservative versus surgical treatment in 961 patients, 12 studies compared the recurrent stroke rate of indirect and direct bypass surgery in 837 patients and 11 papers (1 paper without complication data was excluded) focused on surgical complications after indirect and direct bypass surgery in 1071 patients. Additionally, the mean NOS score was 6.9 indicating that the methodological quality of studies was good (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Some previous studies have suggested that surgery is superior to drugs alone. 7,8 In contrast, Sundaram et al 9 reported that conservative treatment results in a lower stroke recurrence rate and good functional outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…The evidence favours surgical treatment in ischaemic moyamoya and to a lesser extent haemorrhagic moyamoya in which there is an argument that revascularisation may increase the risk of recurrent haemorrhage 42. Available data, however, suggest that revascularisation reduces the risk for recurrent haemorrhage 43. Studies show no significant difference between indirect and direct plus combined techniques 30.…”
Section: Discussionmentioning
confidence: 99%